Adopting sustainable environmental policy based on quadruple helix model in Gorontalo city, Indonesia - Junus, Dikson; Harun, Nur Istiyan; Napir, Suaib (Department of Government Studies, Universitas Muhammadiyah Makassar, 2024)
Gorontalo City is an area that has potential natural resources. However, destructive natural resource management has caused a lot of environmental damage. Waste management, for example, is still a prominent problem in Gorontalo City. This research explains the environmental problems faced by Gorontalo City using the quadruple helix model. This research method uses an explanatory approach, to identify, mapping, and formulating alternative solution models for environmental problems based on sustainable development principles. The data collected is used as input in formulating environmental policies with a collaborative system using the quadruple helix model. The results of the study found that the policy for handling environmental problems in Gorontalo City has not been well optimized. The main problem originates from the lack of a creative and innovative collaboration system between the government, community, academia and industry. Gorontalo City Government basically has a strategic plan, but the formulation, implementation and evaluation process does not involve other strategic actors. The Quadruple Helix model could be a suitable local innovation model that is adjusted to the condition of resources in a local region.